Tính giới hạn \(\lim\limits_{x\to-\infty}\dfrac{\sqrt[3]{x^3+2x^2+1}}{\sqrt{2x^2+1}}\).
\(\dfrac{\sqrt{2}}{2}\) | |
\(0\) | |
\(-\dfrac{\sqrt{2}}{2}\) | |
\(1\) |
Chọn phương án C.
\(\begin{aligned}
\lim\limits_{x\to-\infty}\dfrac{\sqrt[3]{x^3+2x^2+1}}{\sqrt{2x^2+1}}&=\lim\limits_{x\to-\infty}\dfrac{\sqrt[3]{x^3\left(1+\dfrac{2}{x}+\dfrac{1}{x^3}\right)}}{\sqrt{x^2\left(2+\dfrac{1}{x^2}\right)}}\\
&=\lim\limits_{x\to-\infty}\dfrac{x\sqrt[3]{1+\dfrac{2}{x}+\dfrac{1}{x^3}}}{|x|\sqrt{2+\dfrac{1}{x^2}}}\\
&=\lim\limits_{x\to-\infty}\dfrac{x\sqrt[3]{1+\dfrac{2}{x}+\dfrac{1}{x^3}}}{-x\sqrt{2+\dfrac{1}{x^2}}}\\
&=\lim\limits_{x\to-\infty}\dfrac{\sqrt[3]{1+\dfrac{2}{x}+\dfrac{1}{x^3}}}{-\sqrt{2+\dfrac{1}{x^2}}}\\
&=\dfrac{\sqrt[3]{1+0+0}}{-\sqrt{2+0}}=-\dfrac{1}{\sqrt{2}}.
\end{aligned}\)